Meningkatkan Performa Gerakan Kaki pada Atlet Bulu Tangkis Putra U-21: Dampak Latihan Gabungan Plyometrik dan Bayangan - Muhammad Arnando; Nurul Ihsan; Syafruddin Syafruddin; Ardo Okilanda; Yovhandra Ockta (Universitas Nusantara PGRI Kediri, 2025)
Badminton is a high-intensity sport that requires excellent footwork, agility, and explosive movements. Footwork techniques are essential for positioning the body to execute optimal strokes, and deficiencies in this area can negatively affect performance. Plyometric training improves lower-body power and quickness, while shadow training enhances movement patterns and court positioning. Combining these two methods may significantly improve footwork performance, particularly among under-21 male athletes, yet this approach remains underexplored. This study examined the effect of combined plyometric and shadow training on the footwork ability of badminton athletes. A quasi-experimental one-group pretest–posttest design was used, involving fifteen under-21 male badminton athletes from Universitas Negeri Padang selected through purposive sampling based on inclusion criteria of being active, under-21, and injury-free. Participants completed sixteen training sessions of combined plyometric and shadow exercises. Footwork ability was measured before and after the intervention using the validated six-way footwork test with a shuttlecock, recorded manually with a stopwatch. Data were analyzed using SPSS 26, applying normality and homogeneity tests followed by a paired-sample t-test. The results showed a significant improvement in footwork performance (p < 0.05), with most athletes shifting from “poor” in the pretest to “good” or “excellent” classifications in the posttest. These findings demonstrate that the combined training effectively enhanced agility, coordination, and movement efficiency. In conclusion, the integration of plyometric and shadow training provides an effective and engaging approach for improving badminton athletes’ footwork ability and can be recommended for coaches aiming to optimize player performance.